1995
DOI: 10.1152/ajpcell.1995.268.5.c1259
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear proteins bind a cis-acting element in the smooth muscle alpha-actin promoter

Abstract: Identification of the regulators of smooth muscle cell (SMC) gene expression is critical to understanding SMC differentiation and alterations in SMC phenotype in vascular disease. Previous studies revealed positive transcriptional activity within the chicken smooth muscle (SM) alpha-actin promoter region from -209 to -257. In the present study, transient transfections of wild-type and mutant chicken SM alpha-actin promoter/reporter gene constructs into rat aortic SMC demonstrated that the positive transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1998
1998
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…20 Mutation of the single E-box in this upstream region had no effect on the activity of the chicken SM ␣-actin promoter in rat aortic SMC, but the positive activity associated with this region was completely abolished by a 2-bp mutation in a conserved TGTTTATC sequence. 21 Of key importance, results from these studies using a heterologous system are in direct contrast with previous results with this same fragment in a homologous system 20 (chicken SM ␣-actin promoter in chicken SMC) and with a similar fragment of the rat SM ␣-actin promoter in rat SMC. 16 Unlike in the heterologous system, results in the homologous system defined a negative regulatory activity to this promoter region.…”
contrasting
confidence: 64%
See 3 more Smart Citations
“…20 Mutation of the single E-box in this upstream region had no effect on the activity of the chicken SM ␣-actin promoter in rat aortic SMC, but the positive activity associated with this region was completely abolished by a 2-bp mutation in a conserved TGTTTATC sequence. 21 Of key importance, results from these studies using a heterologous system are in direct contrast with previous results with this same fragment in a homologous system 20 (chicken SM ␣-actin promoter in chicken SMC) and with a similar fragment of the rat SM ␣-actin promoter in rat SMC. 16 Unlike in the heterologous system, results in the homologous system defined a negative regulatory activity to this promoter region.…”
contrasting
confidence: 64%
“…Previous studies have shown that mutation of essential nucleotides in the E-box flanking the TGTTTATC element at position Ϫ215 in the chicken SM ␣-actin promoter had no effect on promoter activity. 21 Additionally, in separate studies, we have shown that mutation of either 1 of the 2 E-boxes in the rat SM ␣-actin promoter alone did not affect promoter activity. However, specific mutations in both E-boxes modestly reduced SM ␣-actin promoter activity when transfected into rat aortic SMC.…”
Section: The Repressor Function Of the Tgtttatcccca Element In The Smmentioning
confidence: 81%
See 2 more Smart Citations
“…20 Although the gene is transiently expressed in developing cardiac and skeletal muscle, and in myofibroblasts within tumours and healing wounds, 21,22 in adults it is constitutively expressed solely in VSMCs and smooth musclerelated cells. 23 A number of elements controlling the transcription of VSMC ␣-actin have been defined in the chicken, 24,25 rat, 26,27 mouse [28][29][30] and human [31][32][33] (schematic in Figure 1a). The sequences immediately flanking the VSMC ␣-actin TATA box are highly conserved in human (89% Vs rat), mouse (98% Vs rat), rat and chicken (73% Vs rat) between approximately −255 and +12.…”
Section: Introductionmentioning
confidence: 99%